Sports activities of 60 above Hungarian elderly-explaining and predicting impact of exercise on health - Kinga Lampek; László Csóka; Réka Hegedüs; Miklós Zrínyi; Mária Törőcsik (BMC, 2021)
Abstract Background The proportion of elderly is on the rise both in Europe and in Hungary. The challenge is to increase the number of years spent in good health as well as to improve quality of life of those 60 years and above. This study focuses on the impact of physical activity on this age group. Methods A nationally representative sample of 2000 respondents were surveyed in an age range of 15-74. Our data concerns those being 60-74 years of age. The focus of our investigation was level and impact of physical activity in the group above. First, we used Chi-squared tests and correspondence analysis to identify the deviation in the answers of different groups in our sample. After we built a hierarchical linear regression model to get a deeper understanding of the impact of physical activity for elderly. Results Those reporting no physical/sports activity at all have to do with the negative culture of exercising. Only 9.3% reported being engaged with any sports; 72% reported no regular exercising throughout their lives. The relationship between sport activity and self-reported health was significant (p = 0.009, Cramer's V = 0.2). Elderly were characterized by walking, hiking and less intense sports. Conclusions Those who actively exercised in this research reported better health outcomes than those who stopped or had never been engaged in any sports. We conclude that of all variables tested, physical activity was most effective to improve personal health of the elderly in this sample. Compared to European data on physical activity of elderly populations, Hungary seems to fall behind and needs to consider concentrated efforts to improve the future health of its senior populace.